Prevalence and Risk Factors of Mental Health Symptoms and Suicidal Behavior Among University Students in Wuhan, China During the COVID-19 Pandemic - Xu, Yingying; Su, Sizhen; Jiang, Zhendong; Guo, Suihuai; Lu, Qingdong; Liu, Lin; Zhao, Yimiao; Wu, Ping; Que, Jianyu; Shi, Le; Deng, Jiahui; Meng, Shiqiu; et al. (Frontiers in Psychiatry, 2021)
Background: University students who are exposed to coronavirus disease 2019 (COVID-19) could be mentally distressed. We aimed to evaluate the pattern and risk factors of mental health and suicidal behavior among students who experienced long-term school closure due to the COVID-19 pandemic. Methods: This large-sample, cross-sectional, online survey was conducted from June 29, 2020, to July 18, 2020. 11,254 participants were recruited from 30 universities located in Wuhan, Hubei Province, China. The prevalence of symptoms of depression, anxiety, insomnia, and posttraumatic stress disorder (PTSD) and suicidal behavior was evaluated using the Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, Insomnia Severity Index, Posttraumatic Stress Disorder Checklist for DSM-5, and questions about suicidal ideation and attempts, respectively. Logistic regression was used to explore risk factors for mental health problems and suicidal behavior. Results: The prevalence of mental health problems was 41.5% for depressive symptoms, 32.6% for anxiety symptoms, 35.0% for insomnia symptoms, 8.5% for PTSD symptoms, and 2.0% for suicidal behavior. Participants with high stress during the pandemic were at higher risk of symptoms of depression (adjusted odds ratio [OR] = 1.67, 95% confidence interval [CI] = 1.43-1.95, p < 0.01), anxiety (adjusted OR = 1.90, 95% CI = 1.63-2.23, p < 0.01), insomnia (adjusted OR = 1.64, 95% CI = 1.44-1.87, p < 0.01), PTSD (adjusted OR = 1.71, 95% CI = 1.38-2.11, p < 0.01) and suicidal behavior (adjusted OR = 3.51, 95% CI = 2.28-5.40, p < 0.01). Distant relationship with parents, changes in lifestyle and alcohol use during the pandemic were associated with higher risk of mental health symptoms and suicidal behavior, whereas regular physical exercise reduced the risk of mental health problems. Conclusions: The psychological symptoms and suicidal behavior were relatively high among students who attended university in Wuhan, China after 6 months of the COVID-19 outbreak in China. Comprehensive mental health services and suicide prevention strategies are essential for university students during the COVID-19 pandemic.